Investigation of excitonic recombination and its influence on random lasing phenomenon in ZnO semiconductors - Abiyasa, Agus Putu (2008)
In this thesis, the electronics band structures of wurtzite ZnO bulk materials is studied theoretically based on Empirical Pseudopotential Method (EPM) and 6-band k•p Hamiltonian. Furthermore, confined exciton state in Quantum Wells (QWs) is studied theoretically. By using the k•p Hamiltonian and variational calculation with biaxial strain and exciton-phonon interactions taken into consideration, excitonic optical gain of MgxZn1-xO/ZnO QWs is deduced. From the available experimental data, the band offset and conduction band deformation constant of MgxZn1-xO/ZnO QWs are calculated to be 60/40 and -6.8 eV, respectively. On the other hand, the recombination process due to free exciton state that contributed to random lasing action in highly disordered ZnO polycrystalline films is investigated experimentally. The intrinsic ZnO recombination processes that contribute to random lasing are found to be free-exciton, exciton-exciton scattering or electron hole plasma (EHP) depending on the conditions of ZnO films. The influence of mechanical strain, temperature, and pumping profile on the random lasing mechanisms inside highly disordered ZnO polycrystalline films are then investigated. It is found that 1) the stimulated emission inside ZnO films can be related to free-exciton or EHP depending on the variation of Mott’s density which can be controlled by the mechanical strain, 2) the sustainability of high temperature random lasing action inside ZnO films is due to the strong confinement of excitons inside the ZnO grains and 3) the formation of closed-loop random lasing inside the ZnO films is dependent on optical gain profile which is determined by the operating temperature and pump beam profile.